2015
DOI: 10.1021/acs.est.5b05042
|View full text |Cite
|
Sign up to set email alerts
|

p,p′-DDE Induces Gonadal Intersex in Japanese Medaka (Oryzias latipes) at Environmentally Relevant Concentrations: Comparison with o,p′-DDT

Abstract: Previous studies have reported high body burdens of dichlorodiphenyltrichloroethane (DDT) and its metabolites in wild fishes worldwide. This study evaluated the adverse effects of 1,1-dichloro-2,2-bis (p-chlorophenyl)-ethylene (p,p'-DDE) and o,p'-DDT on gonadal development and reproduction by exposing transgenic Japanese medaka (Oryzias latipes) from hatch for 100 days. While both p,p'-DDE and o,p'-DDT induced intersex in male medaka, the lowest observable effective concentration (LOEC) of o,p'-DDT was 57.7 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
1
34
0
3
Order By: Relevance
“…Vtg1 responded significantly to p,p′-DDE at 1 μM, a concentration previously reported in liver of wild fish (Wan et al, 2005), and close to the lowest observable effective concentration documented in fish after in vivo exposure. Sun et al (2016) (Stanton, 2012). The decrease in pentose sugars and pentose phosphate pathway intermediates may be consistent with a decrease in glucose supply or increased pathway activity to support the demand for NADPH that can be used to support detoxification reactions (e.g., cytochrome P450, glutathione reductase) (Cederbaum, 2015).…”
Section: Pathways Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Vtg1 responded significantly to p,p′-DDE at 1 μM, a concentration previously reported in liver of wild fish (Wan et al, 2005), and close to the lowest observable effective concentration documented in fish after in vivo exposure. Sun et al (2016) (Stanton, 2012). The decrease in pentose sugars and pentose phosphate pathway intermediates may be consistent with a decrease in glucose supply or increased pathway activity to support the demand for NADPH that can be used to support detoxification reactions (e.g., cytochrome P450, glutathione reductase) (Cederbaum, 2015).…”
Section: Pathways Analysismentioning
confidence: 88%
“…p,p′‐DDE exposure considerably impacted the transcription of esr1 and vtg1 in Atlantic salmon hepatocytes. Induction of vtg1 is an established marker of DDE exposure in fish also after in vivo exposure (Monteiro et al, ; Sun et al, ). The same dose–response pattern, with stronger effect at 10 μ m compared to 100 μ m , was also seen in salmon liver cells exposed to bisphenol A and genistein, two compounds that did not affect cell viability at 100 μ m (Olsvik et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Corrosion is also known to be a factor in the selection of materials and surface treatments for medical implants, with metals such as aluminum, iron, magnesium, and carbon steels discarded early on as options due to their reactivity within physiological fluids and tissues . Investigations into how liquid‐infused surfaces can be used to prevent corrosion may suggest pathways to reopen possibilities for the use of these more reactive materials by masking their surface properties with a continuous impermeable liquid layer. Furthermore, the rational design of liquid surface coatings that gradually wear away or dissipate may be used as a mechanism to control the rate of biosorption of magnesium alloys, facilitating the design of resorbable implants or implant parts …”
Section: Applicationsmentioning
confidence: 99%
“…Another study reported that the prenatal exposure (median concentration of 1.2 ng/g lipid) during pregnancy was associated with several adiposity measures in boys [34]. In wildlife, in vivo studies have shown that o,p -DDT can induce intersex in Japanese medaka at much higher exposure concentrations (5−50 µg/L) [35,36]. These studies indicate that the potential toxic concentration of o,p'-DDT for wildlife and humans are at ng/mL level (sub-micro mole level).…”
Section: Tests In Watermentioning
confidence: 99%